APLIKASI PEMBACAAN OBJEK UNTUK IDENTIFIKASI BUKU BERBASIS PENGOLAHAN CITRA - Muhammad Obi Nugraha; Suci Aulia; Atik Novianti (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2020)
Referring to Kamus Besar Bahasa Indonesia (KBBI), the library can be defined as a place for the care and use of books and similar collections that are there. Some collections in the library can be borrowed and brought home within a certain duration. Along with the times, many libraries have used technology to identify books, especially in the process of borrowing books. Some of the technologies that are often used include barcodes and QR codes. Each technology has advantages and disadvantages, we try to take advantage of the image processing process for book identification. The concept proposed is making an application to identify object images based on shapes, colors, and numbers as the identity of a book. The information to be displayed is stored in the database. The image of the object on the front of the book is taken using the camera, after which the system will automatically identify the results of the camera's capture and display the book information according to what is in the database. Application development using Matlab software. Based on the test results, the ideal distance between the object image and the camera is 5 cm with a minimum light intensity of 40 lx and an image resolution of 302x170 px. The average time taken from the camera to take an image until the application displays book information is 0.56 seconds.